Making Environmental SCM Initiatives Work—Moving Beyond the Dyad to Gain Affective Commitment. Issue 1 (28th December 2015) - Wichmann, Barbara K.; Carter, Craig R.; Kaufmann, Lutz; Wilson, Jeffrey R.
Abstract : Companies often struggle to embed environmental sustainability in their supply chain management (SCM) processes due to an insufficient understanding of how to initiate and bring environmental initiatives to fruition. Scholars argue that commitment of employees is crucial to enhance the implementation of these initiatives. Drawing from intra‐organizational influence theory, this study examines how managers who champion these initiatives can gain employee affective commitment within a social network context. Prior research has investigated influence behavior by an individual (an agent) within the organization to gain the commitment of another individual (a target), by focusing on this agent–target dyad. Our research extends this single dyadic agent–target perspective, by investigating influence attempts within a more realistic, multi‐dyadic context in which influence attempts by multiple agents are possible and in fact likely, and in which an actor can be both an agent and a target. We identify a 90‐actor social network, resulting in 273 influence attempts surrounding the implementation of an environmental SCM initiative at a large, multinational corporation, and investigate how the affective commitment of actors in this network is achieved. Based on the analysis of a generalized linear mixed model, the results suggest that if agents want to create a high level of target commitment, then consultation and to a lesser degree inspirational appeals seem to be key, while tactics such as rational persuasion, ingratiation, legitimating, and coalition are not related to affective commitment, within the context of a social network where multiple agents often attempt to influence a target.